Self-Serving Biases in Beliefs about Collective Outcomes - Shimon Kogan; Florian H. Schneider; Roberto A. Weber (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Beliefs about collective outcomes, such as economic growth or firm profitability, play an important role in many contexts. We study biases in the formation of such beliefs. Specifically, we explore whether over-optimism and self-serving biases in information processing—documented for beliefs about individual outcomes—affect beliefs about collective outcomes. We find that people indeed exhibit self-serving biases for collective outcomes, and that such biases are similar to biases for individual outcomes. In addition, we investigate whether collective self-delusion is mitigated by market institutions. If anything, biases in information processing are more pronounced in the presence of a market.
Keywords: I18; C93; Z13; 330; beliefs; Bayes' rule; asymmetric updating; overconfidence; motivated reasoning